Menstrual marks: An evaluative study to assess knowledge and practices among urban and rural adolescent young females of Kanpur, India - Rohan Sachdev; Kriti Garg; Garima Singh (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Menstruation is a unique phenomenon for females. The beginning of menstruation is one of the most significant processes occurring among young females during the adolescent age. AIMS: To assess and compare the real knowledge and practice regarding menstrual marks among adolescent urban and rural young females about menstruation. SETTINGS AND DESIGN: Urban and rural adolescent school young females were selected as participants. SUBJECTS AND METHODS: A school-based, cross-sectional questionnaire study was conducted from June to July 2019 among the adolescent school-going young females of Kanpur who were selected from two urban and five rural schools. All young females aged between 9 and 17 years who have attained menarche were selected and the sample size came out to be 530. STATISTICAL ANALYSIS USED: Collected data were analyzed using IBM SPSS Statistics-version 21. Descriptive statistics included the calculation of percentages. Categorical data were compared using the Chi-square test. All values were considered statistically significant for a value of P < 0.05. RESULTS: 51.8% of rural young females participated in the study. Young females aged 12-14 years were the main participants, and 67.2% of rural and 80.3% of urban young females were aware of menstruation before menarche. Both group young females knew sanitary napkins which were statically significant (P < 0.001). Urban young females were found to be more aware of the menstruation cycle. CONCLUSIONS: Hygienic exercise and knowledge during menstruation were disappointing in the rural area. Rural young females should be more educated about the traditional beliefs and misconceptions regarding menstruation.